2001
DOI: 10.1192/apt.7.4.302
|View full text |Cite
|
Sign up to set email alerts
|

Do women need special secure services?

Abstract: Clinicians working with women patients in secure units will already know that they are the centre of a debate not of their own making, which is about the appropriate specification of services for women patients with security needs. This paper attempts to outline the relevant issues and proposed solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…This is resonant of clinical observations by Watson and Jeffcote (2004), who describe ‘one picture of what women wanted and needed, and another of what [mental health] services were able to offer them’ (p. 11). Bartlett and Hassell (2001) highlighted the dangers of ‘hierarchical’ services ‘feeding into established feelings of powerlessness and exacerbating current illness behaviour’ (p. 307).…”
Section: Discussionmentioning
confidence: 99%
“…This is resonant of clinical observations by Watson and Jeffcote (2004), who describe ‘one picture of what women wanted and needed, and another of what [mental health] services were able to offer them’ (p. 11). Bartlett and Hassell (2001) highlighted the dangers of ‘hierarchical’ services ‘feeding into established feelings of powerlessness and exacerbating current illness behaviour’ (p. 307).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, services are frequently responsible for compounding the past experiences of disempowerment of many service users rather than providing opportunities of acknowledgement, understanding and change.' (Williams et al, 2004: 32) Research has found that women in residential secure services are prescribed more psychoactive drugs than men, and in the case of sedatives and anti-depressants, five times more (Bartlett and Hassell, 2001;Powell, 2001). Women are often believed to contribute to staff stress and burnout due to more frequent incidents of aggression and self harm (Fish, 2000).…”
Section: The Institutional Response To Women In Secure Carementioning
confidence: 99%
“…This reality is often constructed as part of a biological, often medical or social science (Kirk & Hutchins 1999). For example, the distinction made between women who are conceived as ‘mad’ and men who are conceived as ‘bad’ in forensic psychiatry is an example of the medicalization of the felt or experienced consequences of traumatic life events, socio‐economic factors and isolation (Bartlett & Hassell 2001).…”
Section: Contextmentioning
confidence: 99%
“…However, the need for specific mental health services for women has long been contested. Often polarized positions are taken over the risk and benefits of services remaining mainstream and inclusive, or separate, segregated and specialist (Bartlett & Hassel 2001).…”
Section: Introductionmentioning
confidence: 99%